Application of Poka-Yoke in industrial organizations A field study on the Karungi Group of Companies (Journal of University of Babylon for Engineering Sciences, 2018)
The organizations, whether industrial or service, work to eliminate faults and defects in their products. The methods used in the judiciary and the detection of early errors in quality before they occur are Poka Yoke, which prevents unintentional errors and works to detect them. Before they occur through a good design process or the development of techniques. This study is the introduction of a concept of the system of prevention of neglected or unintended errors, which is known as POKA YOKE, its components, and areas of application. Measure the availability and readiness of the field to accommodate such a technique.The statistical program SPSS was used in the analysis of questionnaire data and the researcher reached the possibility of applying this method in the organization in Question.